PRODUCING THE JELLY MADE OF SAMBUNG NYAWA AND STEVIA LEAVESTO DECREASE THE GLUCOSE LEVEL IN THE BLOOD - Wari Tinting Hastuti; Hasna Irfantiningtyas Sari; Athika Wirastiti; Ratnasari -; Saptaka Trihantoro (Pelita - Jurnal Penelitian Mahasiswa UNY, 2013)
This research was aimed to prove whether the jelly of “Sambung Nyawa” leavesand stevia could lower the blood glucose level as an alternative option for people withdiabetes.The method used in this research was a method of diabetes test glucosemonohydrate. In this method glucose monohydrate was induced. The subject in thisresearch was the jelly of “Sambung Nyawa” made of “Sambung Nyawa” leaves as thebasic material added with a natural sweetener made of stevia leaves. The objects ofthis research were Wistar mice. The products of “Sambung Nyawa” jelly and the steviawere given to Wistar mice that had been induced by glucose monohydrate. The ratswere divided into three groups. The first served as a control group, the second groupwas given the same dosage variation, and the third group was a different dosagevariation.Based on the results of this research, it was found out that there was a decreasein the blood sugar levels in the mice that had been induced by glucose monohydrateafter being given the product of “Sambung Nyawa” jelly and stevia. It can be seen fromthe data obtained in the second group. In the group three mice were induced withglucose monohydrate dilution of 1.67 grams with 3 ml of blood sugar levels with anaverage of 82.67 mg / dl blood glucose levels decreased to 90 mg / dl. In the thirdgroup the data could not be retrieved because the mice died before the sugar level waschecked after being induced with glucose monohydrate. Based on the results ofexperimental data it can be concluded that the products of “Sambung Nyawa” jellyand stevia could lower the blood glucose levels. The blood glucose levels weremeasured by using a glucometer.